Perancangan Embedded Web Server Untuk Sistem Monitoring Suhu Dan Kualitas Udder Berbasis Mikrokontroler ATMEGA128 - Sutiana, Aris; Paronda, Abdul Hafid; Sugeng, Sugeng (JREC (Journal of Electrical and Electronics), 2013)
The presence of air quality monitoring in the city was instrumental in the day-to-day human activities which serve to have high mobility. As long as there is still no system that can provide accurate information about the conditions of temperature and air at the site, but this information is needed as a warning and consideration. Although there are tools needed quite complex because it requires a computer server, while the use of server computers are found to be efficient when placed at a location outside the room. Based on the above problems the author to design and create a system of temperature monitoring and web-based air pollution that can be accessed through the medium of computer networks. This web-based monitoring systems embedded in a chip, making it more flexible without needing a computer server. Keyword: Embedded Web Server, Temperature Monitoring, Air Quality Monitoring.